The effect of transmembrane pressure (TMP) towards the harvested rainwater quality - Nur Fariezah , Zaidon (2013)
This thesis discussed about the effect of pressure on the membrane surface towards the quality of harvested rainwater using rainwater harvesting system. The objectives for this research are to determine the characteristics of harvested rainwater and treated water taken from the rainwater harvesting system in Universiti Malaysia Pahang. By testing some parameters which are pH, conductivity, turbidity, colour, total coliform and E.coli, the quality of the water samples taken at the system will be checked whether it is complied with the standard of drinking water which is National Standard of Drinking Water Quality. This thesis also describes the comparison of the characteristics of treated water quality in terms of pressure variation using membrane filtration in Laboratory and Gallery based on several parameters according to the Malaysian National Drinking Water Quality Standards. From the results, the quality of treated water using rainwater harvesting system is believed to become one of the sources of drinking water for people's usage. Other than that, by using the pressure driven membrane processes as the physical treatment for the water treatment, the quality of the treated water can be improvise. By using high pressure on the membrane, the quality of water increase since the contaminants that have been removed by the membrane is higher than using the low pressure since the flux of the water is high. As the results is obtained, it can be concluded that rainwater harvesting system is the water treatment that can be applied on many places even at home and by adding the physical treatment to the system such as membrane filtration, the quality of water produced can be more healthier for the users.